Relationship between attention level and thinking skills of a group of malaysian student teachers - Chua, Y.P. (Common Ground, 2009)
The aim of this survey study was to identify the relationships among paying attention on learning stimuli ability, thinking styles and gender of a group of student teachers (N=147; 49 male, 98 female) from the Kuala Lumpur Special Teacher Training Institute. Two instruments were employed to collect quantitative data from the respondents. The Attention Level Test was used to collect data concerning subjects’ attention levels on verbal stimuli, while the instrument YCRAETIVE-CRITICALS Test was used to collect data of thinking styles of the subjects. Significant results of the one-way ANOVA analyses indicated that lower attention level subjects obtained higher creative thinking style scores [Creative thinking style: High attention level group: M=13.61, SD=3.97; low attention level group: M=21.55, SD=6.51; F(1,145)=55.40, p< .001]. Other results show that male scored higher on creative thinking and lower attention level compared to the female. The findings reveal that the creative male student teachers have less ability of paying attentions to learning stimuli compared to their female counterparts. Since the recent education system in Malaysia emphasizes on logical thinking, rote learning and memorization strategies, the findings of this study can be referred as a case of alternative explanation to the high dropout rate and poor performance of the male students in the higher education institutions in Malaysia.